Innovative Technologies and Technical Means for Industrial Nursery Farming - A. A. Zavrazhnov; A. Yu. Izmaylov; A. I. Zavrazhnov; Ya. P. Lobachevskiy; V. Yu. Lantsev (Сельскохозяйственные машины и технологии)
Russian manufacturing companies do not produce high-clearance equipment for nursery farms growing fruit and berry planting material. In this respect, VIM and Michurinsk State Agrarian University have developed a system of high-clearance machines, taking into account the nursery area, thus providing for effi cient production. (Research purpose) Increasing the effi ciency of growing seedlings and apple rootstocks reproducing in a vegetative way in a mother plantation by means of complex mechanization based on universal technical equipment and technological modules with rational design parameters and kinematic characteristics of working units. (Materials and methods) General methodology for testing machines and working units was supplemented with specifi c methods used in accordance with the research program. The authors made experimental models of machines for spring opening of grafters, cultivating growing shoots, cleaning leaves, and separating branches; provided a system of automatic orientation over a number of plants; and developed a set of technical tools for the care of grafters. (Results and discussion) It has been determined that high-quality spring opening of a mother plantation with the observance of optimal timing for opening shoots increases the productivity of the mother plantation by 7-10 percent. Establishing an optimal environment for plant development using a machine with an active working unit for hilling growing shoots increases the output of standard layering up to 86.2-90.6 percent. Appropriate mechanized separation of layering in improved cutting conditions allowed to increase the yield of standard layering by 5-7 percent, and in the subsequent year there was an 8-10 percent increase in the yield of standard layering (of the fi rst grade) due to their better rooting. (Conclusions) The economic effi ciency of using a universal mechanized set of machinery in a mother plantation is from 514 thousand to 664 thousand rubles per one hectare. The use of high-level technical means of SUVES, VP-1.5 and AP-1.5 with replaceable technological modules increases the level of mechanization by an average of 30 percent, signifi cantly reduces labor costs – up to 20 percent, and improves working conditions for operating staff .